Evaluating Associations Between Nonclinical Cardiovascular Functional Endpoints and Repeat-dose Cardiovascular Toxicity in the Beagle Dog: A Cross-company Initiative. (16th April 2020) - Milliken, Philip; Aylott, Mike; Edmunds, Nick; Engle, Steven; Ewart, Lorna; Fleurance, Renaud; Guffroy, Magali; Hargreaves, Adam; Heinz-Taheny, Kathleen; Kirk, Sarah; Leishman, Derek; Leong, Louise; et al.
Abstract: Integrating nonclinical in vitro, in silico, and in vivo datasets holistically can improve hazard characterization and risk assessment. In pharmaceutical development, cardiovascular liabilities are a leading cause of compound attrition. Prior to clinical studies, functional cardiovascular data are generated in single-dose safety pharmacology telemetry studies, with structural pathology data obtained from repeat-dose toxicology studies with limited concurrent functional endpoints, eg, electrocardiogram via jacketed telemetry. Relationships between datasets remain largely undetermined. To address this gap, a cross-pharma collaboration collated functional and structural data from 135 compounds. Retrospective functional data were collected from good laboratory practice conscious dog safety pharmacology studies: effects defined as hemodynamic blood pressure or heart rate changes. Morphologic pathology findings (mainly degeneration, vacuolation, inflammation) from related toxicology studies in the dog (3–91 days repeat-dosing) were reviewed, harmonized, and location categorized: cardiac muscle (myocardium, epicardium, endocardium, unspecified), atrioventricular/aortic valves, blood vessels. The prevalence of cardiovascular histopathology changes was 11.1% of compounds, with 53% recording a functional blood pressure or heart rate change. Correlations were assessed using the Mantel-Haenszel Chi-square trend test, identifying statistically significant associations between cardiac muscle pathology and (1) decreased blood pressure, (2) increased heart rate, and between cardiovascular vessel pathology and increased heart rate. Negative predictive values were high, suggesting few compounds cause repeat-dose cardiovascular structural change in the absence of functional effects in single-dose safety pharmacology studies. Therefore, observed functional changes could prompt moving (sub)chronic toxicology studies forward, to identify cardiovascular liabilities earlier in development, and reduce late-stage attrition.